ANALISIS PENDISTRIBUSIAN DANA ZAKAT, INFAQ, DAN SEDEKAH (ZIS) YANG TIDAK PRODUKTIF DI INDONESIA - Sakinah Fakiriyah; Nabila Hana; Agung Ramadani; Maya Panorama (CV. Doki Course and Training, 2023)
The purpose of this study is to examine how ZIS zakat, infaq, and alms funds are distributed ineffectively in Indonesia. In this study, a qualitative approach was combined with a descriptive methodology. Planning, structuring, serving, and managing are all involved in almsgiving, zakat distribution, and infaq distribution. ZIS money is distributed to individuals who are eligible to receive it, or ZIS is distributed. Through the body in charge of zakat, cash will be channeled from muzzaki to mustahiq. To keep human property, property, and soul in a state of fitrah, zakat has two purposes. In addition, it serves as a communal fund used for charitable purposes. Zakat funds can be distributed in various ways, including individually or through amili zakat organizations such as BAZNAS. There is still a need for improvement in the zakat distribution method used by many zakat amyl institutions. Some ZIS payments are not evenly distributed as a result of this zakat distribution mechanism. Abstrak Tujuan dari penelitian ini adalah untuk mengkaji bagaimana dana zakat, infaq, dan sedekah ZIS disalurkan secara tidak efektif di Indonesia. Di dalam penelitian ini, pendekatan kualitatif dikombinasikan dengan metodologi deskriptif. Perencanaan, penataan, penjabatan, dan pengelolaan semuanya terlibat dalam pemberian sedekah, penyaluran zakat, dan penyaluran infaq. Uang ZIS didistribusikan kepada individu yang memenuhi syarat untuk menerimanya, atau ZIS didistribusikan. Melalui badan yang bertugas zakat, uang tunai akan disalurkan dari muzzaki ke mustahiq. Untuk menjaga harta benda, harta, dan jiwa manusia dalam keadaan fitrah, zakat memiliki dua tujuan. Selain itu, ini berfungsi sebagai dana komunal yang digunakan untuk tujuan amal. Dana zakat dapat disalurkan dengan berbagai cara, termasuk secara individu maupun melalui organisasi amili zakat seperti BAZNAS. Masih perlu perbaikan dalam metode penyaluran zakat yang digunakan oleh banyak lembaga zakat amil. Beberapa pembayaran ZIS tidak tersebar merata sebagai akibat dari mekanisme penyaluran zakat ini.